2005
DOI: 10.1108/10662240510602672
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of online gaming crime characteristics

Abstract: Purpose-To arouse the public awareness of online gaming-related crimes and other societal influences so that these problems can be solved through education, laws and appropriate technologies. Design/methodology/approach-A total of 613 criminal cases of online gaming crimes that happened in Taiwan during 2002 were gathered and analyzed. They were analyzed for special features then focusing on the tendency for online gaming crime. Related prosecutions, offenders, victims, criminal methods, and so on, were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 2 publications
0
30
0
2
Order By: Relevance
“…5,6 Previous studies of online gaming addiction have mainly addressed addicts' psychological motives [7][8][9] and profiles of gamers. 5,10,11 In contrast, research focused on changing adolescent players' attitudes toward online gaming has been rare. Online game players' attitudes may play a critical role in determining the motives and meanings of their involvement and addictive behaviors.…”
Section: Introductionmentioning
confidence: 85%
“…5,6 Previous studies of online gaming addiction have mainly addressed addicts' psychological motives [7][8][9] and profiles of gamers. 5,10,11 In contrast, research focused on changing adolescent players' attitudes toward online gaming has been rare. Online game players' attitudes may play a critical role in determining the motives and meanings of their involvement and addictive behaviors.…”
Section: Introductionmentioning
confidence: 85%
“…Chen, et al (2005) found in their analysis of online gaming crime that 46.7% of the offenders were students and that most of these crimes were committed from public computer use areas such as Internet cafes. In fact, they stipulated in their work, which is now almost a decade old, that "such cyber-criminal activity within online games is increasing at an alarming rate" (Chen, et al, 2005). They found that the use of another person's online gaming account (and subsequent theft of their property within the game) without their permission was 73.7% of all computer gaming crime reviewed.…”
Section: Routine Activities Theory Pdos and Unethical Student Onlinmentioning
confidence: 99%
“…Although the percentage playing online games was smaller (38% of surveyed students), this is still a significant portion of the overall student population who are familiar with the use of the Internet to play a game against a distant opponent. Even several years ago, Chen, et al (2005) noted that with the growth of online gaming, there was a corresponding growth in gaming-related crimes, and particularly in MMOG games.…”
Section: Routine Activities Theory Pdos and Unethical Student Onlinmentioning
confidence: 99%
“…In an examination of 613 online gaming criminal cases, occurring during 2002 in Taiwan it was found that theft and fraud were the major type of online gaming crimes [11]. 73.7% of cases were charged with theft, while 20.2% were charged with fraud [11].…”
Section: Transfer Mechanics Of Virtual Propertymentioning
confidence: 99%
“…73.7% of cases were charged with theft, while 20.2% were charged with fraud [11]. These criminal cases came from official crime reports, from different judicial or investigative authorities [11].…”
Section: Transfer Mechanics Of Virtual Propertymentioning
confidence: 99%